MENINGKATKAN KETERAMPILAN MEMBACA DENGAN PENERAPAN MEDIA GAMBAR SISWA KELAS II MIN 7 SELUMA - Jonior Asmara; Reni Kusmiarti (Jurnal Membaca (Bahasa dan Sastra Indonesia), 2026)
This study aims to determine the effectiveness of using visual media in improving the reading skills of second-grade students at MIN 7 Seluma. This study used a quantitative approach with an experimental method and a One Group Pretest-Posttest design. Twenty second-grade students participated in the odd semester of the 2024/2025 academic year. Data were collected through reading tests (pretest and posttest), activity observation sheets, and documentation. The test instruments covered aspects of pronunciation accuracy, intonation, loudness, and reading confidence. Data were analyzed using a t-test to determine significant differences between the pretest and posttest results.The results showed an improvement in reading skills after using visual media. The average pretest score of 71.94 increased to 87.71 in the posttest. In addition to the increase in the average, the distribution of student ability categories also shifted from a predominance of the adequate category to a majority in the good and excellent categories. These findings demonstrate that visual media is effective in helping students read more fluently, use appropriate intonation, and improve reading comprehension